Tax Avoidance in the Energy Sector: The Influence of Corporate Social Responsibility, Company Size, Profitability - Dika Puspitaningrum; Muhammad Syihabuddin; Fatah Mario Andaru (International Journal of Entrepreneurship, Business, and Creative Economy, 2026)
This study examines the relationships among Corporate Social Responsibility (CSR), firm size, and profitability, and tax avoidance, proxied by CETR, in energy sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023, using multiple linear regression analysis. The total sample used is 69 companies. Empirically, the findings indicate that higher levels of CSR disclosure are associated with lower Cash Effective Tax Rates (CETR), indicating greater levels of tax avoidance. These results provide empirical support for legitimacy-based arguments in the tax avoidance literature, which suggest that CSR disclosure can serve as a strategic mechanism to offset reputational risks arising from aggressive tax practices. In contrast, firm size, as measured by total assets, was found to have no significant effect on tax avoidance, indicating that firm size alone does not determine tax planning behavior in the energy sector. Furthermore, profitability exhibits a significant negative relationship with tax avoidance, indicating that firms with stronger financial performance tend to adopt more conservative tax positions, possibly due to greater regulatory and stakeholder scrutiny. By focusing on energy sector firms and using CETR as a cash-based proxy for tax avoidance, this study extends previous empirical evidence on the heterogeneous roles of CSR and profitability in corporate tax behavior and provides sector-specific insights into the existing tax avoidance literature in the context of emerging markets.